Support opportunities for second victims lessons learned: a qualitative study of the top 20 US News and World Report Honor Roll Hospitals - Ruby Marr; Anupama Goyal; Martha Quinn; Vineet Chopra (BMC Health Services Research, 2021)
Abstract Background Second Victim Programs (SVPs) provide support for healthcare providers involved in a near-miss, medical error, or adverse patient outcomes. Little is known about existence and structure of SVPs in top performing US hospitals. Methods We performed a prospective study and interviewed individuals representing SVPs from 20 US News and World Report (USNWR) Honor Roll Hospitals. Telephone interviews were recorded, transcribed, and de-identified. To allow identification of both quantitative and qualitative themes that unified or distinguished programs with SVPs from each other, a content analysis approach was used. Results Of the Top 20 UNSWR hospitals, nineteen individuals with knowledge of or involvement in SVPs were identified. One individual represented two hospital systems for the same institution. Thirteen representatives agreed to participate, 12 declined, and 5 did not respond. One individual who initially agreed to participate did not attend the interview. Among twelve representatives interviewed, 10 reported establishment of SVPs at their hospitals between 2011 and 2016. Most program representatives reported that participants sought support voluntarily. Four domains were identified in the qualitative analysis: (a) identification of need for Second Victim Program (SVP); (b) challenges to program viability; (c) structural changes following SVP creation, and (d) insights for success. Driving SVP creation was the need support medical providers following a traumatic patient event. Poor physician participation due to the stigma associated with seeking support was commonly reported as a challenge. However, acceptance of the mission of SVPs, growing recognition of the value of the program across hospital departments, and systematic safety enhancements were cited as key advantages. To ensure success, participants suggested training a variety of volunteers and incorporating SVPs within quality improvement processes. Conclusions In this convenience sample, programs for healthcare providers that experience psychosocial or emotional trauma from clinical care were uncommon. Variation in structure, performance, and measures of success among SVPs was observed. A systematic approach to evaluating SVPs is needed to help inform institutions of how to best serve their second victims.